15(x)=6+14(x)

Simple and best practice solution for 15(x)=6+14(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15(x)=6+14(x) equation:


Simplifying
15(x) = 6 + 14(x)

Solving
15x = 6 + 14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14x' to each side of the equation.
15x + -14x = 6 + 14x + -14x

Combine like terms: 15x + -14x = 1x
1x = 6 + 14x + -14x

Combine like terms: 14x + -14x = 0
1x = 6 + 0
1x = 6

Divide each side by '1'.
x = 6

Simplifying
x = 6

See similar equations:

| 2(x+2)=-6 | | -832=56b+356 | | 224=(W-8)+W+(W-8)+W | | -2(n-7)=-6 | | 16m-7m=18 | | 128=(W-8)+W+(W-8)+W | | 12q-7q=20 | | 3x^2+10=110+x^2 | | 7x+5=3x+17-3x | | ((cos^2)(x))+2cosx+1=0 | | -8+5b+7=b+5+6 | | 8*1-18= | | -18m+6m-2m=14 | | -2(3n-5)-(3-4n)=-3 | | -X+2(1)=6 | | -8x=10-(-14) | | 7h-(-8h)-16h=17 | | (15a+3b)+(a+3b-4)= | | 2=1k+-32 | | 6x-3=4x+3+2x | | (2x-6)+(x-3)= | | 20x-8=11x+2 | | 2x-5=x-(5x-7) | | 8(5+t)-6(t+2)= | | 4x+10x=10 | | -0.7x-1.75=1.7+0.8x | | 8(-1)-18= | | 2x-5=x-(5-7) | | 1.24*0.2= | | -14u+2u+12u+-u=16 | | -5n-2n=13 | | -5.2q+1.9=-27.8-1.9q |

Equations solver categories